The effect of low-electrical voltage as a method to eradicate Acinetobacter baumannii bacteria - Putri, Naomi Lesmana; Koendhori, Eko Budi; Susilo, Imam; Tambunan, Betty Agustina (Journal of Clinical Microbiology and Infectious Diseases, 2023)
Introduction: Acinetobacter baumannii is one of the bacteria in critical priority according to WHO in 2017 and one of the causes of nosocomial infections in the world. These bacteria usually become resistant to antibiotics (Multi Drug Resistant Organism, MDRO), infect the bloodstream, and cause pneumonia. This study aimed to examine the effect of low-voltage electricity as a method to kill Acinetobacter baumannii by using a different electric current. Methods: This study is experimental research in the Microbiology Laboratory of RSAB Harapan Kita. Experiments were carried out using a solution of Acinetobacter baumannii non-MDRO and MDRO bacteria with a parallel design device opposite to the GPS 3030D power supply with a power of 90 W. Each tube was fitted with a 12 cm stainless steel rod conductor with a diameter of 3 mm and delivered amperage 1 mA, 2 mA, 5 mA, and 10 mA and 0.5V with each amperage performed 5 times and measured using DensiCHEK. Result: From 20 Acinetobacter baumannii non-MDRO experiments and 20 MDRO experiments, it was found that from 1 mA, 2 mA, 5 mA, and 10 mA with monitoring time of 30 minutes, 2 hours, and 4 hours, the results of bacterial eradication by DC stimulation with 5 mA and the most optimal time is 30 minutes according to what has been applied. Conclusion: Using an electric current of 5 mA and a duration of 30 minutes can reduce Acinetobacter baumannii MDRO and non-MDRO bacteria with more optimal results in the non-MDRO group.